Strategies to Enhance Drug Permeability across Biological Barriers - Wen, Jingyuan; Huang, Yuan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Overcoming biological barriers is a significant challenge in drug development, and recent advancements in drug delivery systems and technologies offer promising solutions. This Special Issue highlights the innovative approaches and techniques being used to improve drug permeability and absorption, as well as their potential impact on a wide range of therapeutic goals. These advancements being made in drug delivery and permeability offer exciting possibilities to improve patient outcomes.